Physiological and Biochemical Response of Tropical Fruits to Hypoxia/Anoxia - Benkeblia, Noureddine (Frontiers in Plant Science, 2021)
Aerobic respiration and oxygen consumption are indicators of routine metabolic rate (RoMR), and dissolved oxygen in plant tissues is one of the most important environmental factors affecting their survival. The reduction of available O2 leads to hypoxia which causes a limitation of the oxidative phosphorylation; when O2 is absent, tissues generate ATP by activating the fermentative glycolysis to sustain glycolysis in the absence of mitochondrial respiration, which results in the production of lactate. Overall, hypoxia was reported to often decrease the respiration rate (O2 uptake) and delay the climacteric rise of ethylene in climacteric fruits by inhibiting action, thus delaying their ripening. Much research has been done on the application of postharvest hypoxia and anoxia treatment to temperate fresh crops (controlled or modified atmosphere), however, very few reported on tropical commodities. Indeed, the physiological mode of action of low or absence of oxygen in fresh crops is not well understood; and the physiological and biochemical bases of the effects low or absence of O2 are also yet to be clarified. Recent investigations using omics technologies, however, have provided useful information on the response of fresh fruits and vegetables to this abiotic stress. The aims of this review are to (i) report on the oxygen exchange in the crops tissue, (ii) discuss the metabolic responses to hypoxia and anoxia, and (iii) report the physiological and biochemical responses of crops tissues to these abiotic stresses and the potential benefits of these environmental conditions.